THE SYMBOLS OF THE CHARACTERISTICS OF GREEK MYTHOLOGYCAL GODDESSES IN RITA DOVEâ€™S â€œDEMETER WAITINGâ€ AND â€œPERSEPHONE, FALLINGâ€ - Risca Irja Hanani (Universitas Katolik Widya Mandala Surabaya, 2015)
This article discusses the characteristics of the Goddesses of Greek Mythology through the symbols in Rita Doveâ€™s â€œDemeter Waitingâ€ and â€œPersephone, Fallingâ€. The aim of this article is to analyze the symbols dealing with the characteristics of the Goddesses of Greek Mythology in Rita Doveâ€™s â€œDemeter Waitingâ€ and â€œPersephone, Falling.â€ The technique that is used to collect the data is library research. The data consists of the ideas related to the characteristics of the Goddesses of Greek Myhtology that are symbolized through Rita Doveâ€™s poems. The theory of meaning, symbol, and character were applied in this research. Moreover, the approches that were used are structural aproach, sociological approach, moral approach, and philosophycal approach. The result of thsi article is on Demeterâ€™s characteristics which are describe as they are being passionate in teaching her daughter, being maternal, and being protective by sacrificing herself for Persephone. Next, it also tells about Persephoneâ€™s characteristics, that is, unadorned, stubbrn, and unstable emotionally. Furthermore, by analyzing the characteristics and the symbols of those goddesses, the researcher knows that their characteristics represent mother and daughter relationship in which they always protect each other. Key Words: Greek Mythologi, symbol, character